Per-oral Endoscopic Myotomy (POEM) After the Learning Curve: Durable Long-term Results With a Low Complication Rate. Issue 3 (September 2016) - Hungness, Eric S.; Sternbach, Joel M.; Teitelbaum, Ezra N.; Kahrilas, Peter J.; Pandolfino, John E.; Soper, Nathaniel J.
Abstract : Objective: We aimed to report long-term outcomes for patients undergoing per-oral endoscopic myotomy (POEM) after our initial 15-case learning curve. Background: POEM has become an established, natural-orifice surgical approach for treating esophageal motility disorders. To date, published outcomes and comparative-effectiveness studies have included patients from the early POEM experience. Methods: Consecutive patients undergoing POEM after our initial 15 cases, with a minimum of 1-year postoperative follow-up, were included. Treatment success was defined as an Eckardt score ⩽3 without reintervention. Gastroesophageal reflux was defined by abnormal pH-testing or reflux esophagitis >Los Angeles grade A. Results: Between January 2012 and March 2015, 115 patients underwent POEM at a single, high-volume center. Operative time was 101 ± 29 minutes, with 95% (109/115) of patients discharged on postoperative day 1. Clavien-Dindo grade III complications occurred in 2.7%, one of which required diagnostic laparoscopy to rule out Veress needle injury to the gall bladder. The rate of grade I complications was 15.2%. At an average of 2.4 years post-POEM (range 12–52 months), the overall success rate was 92%. Objective evidence of reflux was present in 40% for all patients and 33% for patients with a body mass index <35 kg/m 2 and no hiatal hernia. Conclusions: POEM performed by experienced surgeons provided durable symptomatic relief in 94% of patients with nonspastic achalasia and 90% of patients with type 3 achalasia/spastic esophageal motility disorders, with a low rate of complications. The rate of gastroesophageal reflux was comparable with prior studies of both POEM and laparoscopic Heller myotomy.